DEVELOPMENT OF MATHEMATICS COMIC MEDIA BASED ON REALISTIC MATHEMATICS EDUCATION TO IMPROVE PROBLEM-SOLVING ABILITY STUDENT OF SEVENTH GRADE OF MIDDLE SCHOOL 7 PADANGSIDIMPUAN SCHOOL YEAR 20202021 - Masleni Harahap; Hasratuddin Siregar; Evi Eviyanti (SENSEI RESEARCH CENTER, 2022)
This study aims to: 1) Analyse the improvement of mathematics problem-solving ability student of eventh grade of middle school 7 Padangsidimpuan school year 2020-2021. 2) Finding effectiveness of methematical Comic media based realistics mathematic education to improve mathematics problem-solning ability student of eventh grade of middle school 7 Padangsidimpuan school year 2020-2021. 3) Describe characteristics of Comic media based on realistic mathematics education to improve mathematics problem-solving ability student of eventh grade of middle school 7 Padangsidimpuan school year 2020-2021. The study was designed by as a development research 4-D method by Thiagajaran, Semmel dan Semmel. It was found that there are developments in define, design, develop, and dessiminate. The result of the study show: There are 8 (30.8%) students whose level of mathematical problem solving ability is in the low category, 16 (61.5%) students are classified as moderate, and 2 (7.7%) students are high. The results of the second trial there were 5 (17.85%) students whose mathematical problem-solving abilities were in the low category, 21 (75%) students belonged to the medium category, and 2 (7.17%) students who were classified in the high category;2) the mathematical comic media based on a realistic approach meets the valid and effective criteria in terms of their respective criteria; 3) The characteristics of comic media based on realistic mathematics education stated on: 1) using of the contextual problems; 2) using of the learning models; 3) using of the student contributions; 4) interactive; 5) related to other topics.